Environmental Impact of Community-Based Waste Management Study in Plosojenar Village, Ponorogo Regency - Sukoco, Johan Bhimo; Wijaya, Andy Fefta; Mindarti, Lely Indah; Nuh, Mohammad (Universitas 17 Agustus 1945 Surabaya, 2024)
Community empowerment in waste management is a strategy for creating a clean and sustainable environment. Community-based waste management is expected to have an environmental impact, thereby creating a sustainable environment. This research aims to describe and analyze the environmental impact of community-based waste management through community empowerment in Plosojenar Village, Ponorogo Regency. This research is a qualitative descriptive study. Data collection techniques use interviews, observation, documentation, and Focus Group Discussions (FGD). Triangulation of sources and methods was used to test the validity of the data. Data analysis uses Creswell's qualitative analysis model. The research results show that community-based waste management has the opportunity to encourage environmental impact, by empowering the community through the Maesojenar Compost House. Various programs have been designed, such as: Coconut Fiber Waste Processing Program, Compost Fertilizer Processing Program, and Waste Savings Program. In the future, the sustainability of this program needs to be considered. Apart from that, the use of social media needs to be strengthened to voice issues surrounding waste management, so that it can encourage the creation of good environmental impacts.